2018
DOI: 10.1186/s13104-018-3406-6
|View full text |Cite
|
Sign up to set email alerts
|

Imipenem resistance in clinical Escherichia coli from Qom, Iran

Abstract: ObjectiveThe emergence of metallo-β-lactamase-producing Enterobacteriaceae is a worldwide health concern. In this study, the first evaluation of MBL genes, blaIMP and blaVIM, in Escherichia coli resistant to imipenem isolated from urine and blood specimens in Qom, Iran is described. Three hundred urine and blood specimens were analysed to detect the presence of E. coli. Resistance to imipenem and other antimicrobials was determined by disk diffusion and MIC. MBL production was screened using CDDT. PCR was also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 35 publications
3
11
2
Order By: Relevance
“…In our study, the highest and lowest resistance rates were observed against imipenem (56.1%) and fosfomycin (15%), respectively. Previously, a survey reported a 3% rate of resistance to imipenem in Iran [25], which is much lower than the rate observed in our study. However, the survey included isolates from both blood and urine samples.…”
Section: Discussioncontrasting
confidence: 92%
“…In our study, the highest and lowest resistance rates were observed against imipenem (56.1%) and fosfomycin (15%), respectively. Previously, a survey reported a 3% rate of resistance to imipenem in Iran [25], which is much lower than the rate observed in our study. However, the survey included isolates from both blood and urine samples.…”
Section: Discussioncontrasting
confidence: 92%
“…In positive cases of Shigella spp. and Salmonella spp., an agglutination reaction was observed between the antigen and antibody (12)(13)(14). Other biochemical methods (e.g., esculin hydrolysis, DNase, coagulase, catalase, hemolysis, growth on 6.5% NaCl, and susceptibility to optochin) were also used for the detection of the Gram-positive bacteria (15,16).…”
Section: Isolation and Detection Of The Bacteriamentioning
confidence: 99%
“…In this study, 80.9% of the urinary isolates of E. coli were MDR, which was very similar to the study performed in Ahwaz (22). In the research of Badamachi et al, (18), 54.6% of urinary isolates were MDR, while only 1 to 5-year-old children were studied. Since the prevalence of MDR E. coli strains, especially in burn patients, can increase morbidity and mortality rates (29), so their presence can be a major risk factor for the patients.…”
Section: Discussionmentioning
confidence: 99%